Resource-efficient piston ring/cylinder liner pairing. Issue 1 (4th December 2018) - Risse, Konstantin; Schorgel, Matthias; Bartel, Dirk; Karpuschewski, Bernhard; Welzel, Florian
Abstract : Purpose: The purpose of this paper is to investigate the influence of different finish processes on the surface integrity and tribological behaviour of cylinder running surfaces for internal combustion engines. Design/methodology/approach: The cutting force during finishing and the resulting surface topography was measured for a variety of cylinder running surfaces made of EN-GJL-250, EN-GJV-400 and thermal sprayed aluminium alloy. A separate conditioning tool was developed and tested. Different analysis methods (SEM, EDX, SIMS and FIB) for the characterisation of the boundary conditions were used. By an oscillating friction wear test and a single cylinder floating liner engine, the running-in and frictional behaviour was rated. Findings: It was shown that honing with low cutting forces and silicon carbide cutting material decreases the friction in operation. The characteristics of the boundary layers after running-in depend on the finish machining process. A preconditioning with a separate tool can adjust the boundary layer and running-in behaviour. Based on the experimental results, a multi-body and computational fluid dynamics simulation was developed for the floating liner engine. Originality/value: The results demonstrate the potential of finishing with low process forces to reduce friction and the need for a complete consideration of the tribological system piston ring/cylinder liner surface.